Závislost mimetické podobnosti myrmekomorfních pavouků na nechutnosti modelu - Dobrovodský, Juraj (Jihočeská univerzita, 2018)
Widely known fact is the generalist predators are averse to ants. This is the reason why more than 300 species of spiders choos special life strategy myrmecomorphy. In my master thesis I tested proteective quality of myrmecomorphyof Phrurolithus festivus compared whith cricket Gryllus assimilis, non-myrmecomorph spider Lycosa sp young nymps and Lasius niger ants. The chosen predator was great tit Parus major. This is the first time when vertebrate predator was used for testing myrmecomorphy. In the experiment great tits choose between combination of two preys. These combinations were ant-cricket, non-myrmecomorp spider-myrmecomorph spider, ant myrmecomorph spider. I was interested in two facts: for first how long time grat tits spend by detecrement between both of the preys and for second which prey was choosen. The time while great tits recognize the prey was short and very similar for all of the experiments. The difference was not significant. In the prey choice experiment for first, great tits prefer crickets before ants. In comparison experiment bitween myrmecomorp spider non-mrmecomorp spider great tits unambigously choose common spider, the myrmecomorph spiders were not attacked. Experiment whit myrmecomorph spider and ant show us the protection of myrmecomorphy is good but not perfect. Both of them was choosen, but still less commonly then other edible preys in experiments above. This experiment show me antoher interesting fact. While great tit choose between ant and myrmecomorp in time they came to be more inaccurate. Quite commonly choose ants on the and of experimental series. It maybe means the protection leads tits to incorrect choice. This experiment shown us, the myrmecomorph protection of the P. festuvis is functional, but it depends on enviroment and the comparison. I believe protection of spider greatly work on field, because tits do not have chance to make comparison and the enviroment is more dissected and dispersive.
Relationship of myrmecomorph spiders, ants and predators
Keywords: myrmekomorfie; mimikry; Phrurolithus sp; Lasius sp; sýkora koňadra; predace; maskovaní; myrmecomorphy; mimicry; Phrurolithus sp; Lasius sp; great tit; predation; masquarade